1967
DOI: 10.1113/jphysiol.1967.sp008251
|View full text |Cite
|
Sign up to set email alerts
|

The partition of sodium fluxes in isolated toad oocytes

Abstract: 2. The mean rate constant for Na efflux was 6-4 x 10-3 min-' corresponding to an apparent Na efflux rate of 13-3 p-mole/cm2. sec. When this is corrected for the increase in surface area produced by microvilli the true efflux rate is 1F1-1-3 p-mole/cm2.sec.3. The action of ouabain (1-5,M) appears to involve two different effects: (a) there is 48-65 % inhibition of the membrane Na pump, and (b) there is a release of some of the sequestered Na in the cell.4. Removal of external K causes a 40 % reduction in Na eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1970
1970
1984
1984

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…From the speed of penetration of 22Na into the cytoplasm and the small effect of halving or doubling the temperature on the rate of exchange, Abelson & Duryee (1949) concluded that the plasma membrane exerted little control over sodium movement in their cells. On the other hand the effect of inhibitors and changes in temperature (Dick & Lea, 1967;Bittar, Dick & Fry, 1968) suggested that active transport in the cell membrane had a pronounced effect on Na movement in cells similar to those used in this work. These discrepancies are not due to species differences between frogs and toads since recent results on frog oocytes are similar to these obtained with toads (D. A. T. Dick & E. G. Dick, unpublished Appleton (1966) examined the fall-off in grain density at the edge of cryostat sections labelled with 22Na.…”
Section: Discussionmentioning
confidence: 87%
“…From the speed of penetration of 22Na into the cytoplasm and the small effect of halving or doubling the temperature on the rate of exchange, Abelson & Duryee (1949) concluded that the plasma membrane exerted little control over sodium movement in their cells. On the other hand the effect of inhibitors and changes in temperature (Dick & Lea, 1967;Bittar, Dick & Fry, 1968) suggested that active transport in the cell membrane had a pronounced effect on Na movement in cells similar to those used in this work. These discrepancies are not due to species differences between frogs and toads since recent results on frog oocytes are similar to these obtained with toads (D. A. T. Dick & E. G. Dick, unpublished Appleton (1966) examined the fall-off in grain density at the edge of cryostat sections labelled with 22Na.…”
Section: Discussionmentioning
confidence: 87%
“…Analysis of the kinetics of Na movements in toad oocytes (Dick & Lea, 1964, 1967 has suggested that there exists a fraction of Na in the oocyte whose rate of exchange with external or internal Li is virtually zero, and whose rate of exchange with the remaining internal Na is reduced. Measurements of Na activity in the oocyte by means of Na sensitive microelectrodes (Dick & McLaughlin, 1969) have pointed to the same conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Ouabain treatment of the oocytes caused an approximately 37% rise in the total Na concentration, consistent with the 50 -60% inhibition of the Na pump by ouabain described in Bufo bufo oocytes by DICK and LEA (13). On the other hand, inhibition of the Na pump by ethacrynic acid results in 60% rise in total Na concentration, in agreement with the previous studies of BITTAR, DICK and FRY (3) who showed that ethacrynic acid is a potent inhibitor of Na pump.…”
Section: Measurement On Oocytes (Bufo Bufo)mentioning
confidence: 64%